Effectiveness of the Heads of Schools in Managing Financial Resources in Public Secondary Schools in Moshi Municipality - Edmund, Samwel; Lyamtane, Rev. Dr. Eugene (International Journal of Scientific Research and Management (IJSRM), 2018)
This study examined the effectiveness of the Heads of Secondary Schools in Managing Financial Resources in Public Secondary Schools in Moshi Municipality.  It was guided by the following research questions:  To what extent do Heads of Schools implement the procedures in managing Schools finances?   What are the procedures of disbursing, ensuring safe custody, procurements and payments of the School finances?  What are the challenges facing head of schools in managing financial resources in secondary schools in Moshi municipality? What should be done to improve the management of financial resources in secondary school in Moshi Municipality?  This study was quantitative research which employed cross sectional design.  Stratified and simple random sampling procedures were used to obtain the participants. The instruments which were used in data collection were questionnaires, interview schedule and observation schedule. The researcher used quantitative methods to analyze data. The Statistical Package for Social Sciences (SPSS version 16) was used to generate data that was used to test the hypotheses. One way ANOVA was used to test all hypotheses.  Findings show that Heads of schools do not adhere to the financial guidelines given out by the Government.  Also procurements procedures at School are not adhered as the Government guidelines direct. The findings as well show that, financial documents management in Public Secondary Schools in Moshi Municipality does not follow the Government directives. Basing on the findings the following were concluded; Heads of Schools are ineffective and perform poorly in managing the school financial resources.  They do not adhere to the procurement procedures given by the Government and perform at satisfactory level on disbursing and payments procedures of the School funds.